Life without money : building fair and sustainable economies - Nelson, Anitra; Timmerman, Frans (Pluto Press, 2011)
The money-based global economy is failing. The credit crunch undermined capitalism's ability to ensure rising incomes and prosperity while market-led attempts to combat climate change are fought tooth and nail by business as environmental crises continue. We urgently need to combat those who say "there is no alternative" to the current system, but what would an alternative look like? The contributors to Life Without Money argue that it is time radical, non-market models were taken seriously. The book brings together diverse voices presenting strong arguments against our money-based system's ability to improve lives and prevent environmental disaster. Crucially, it provides a direct strategy for undercutting capitalism by refusing to deal in money, and offers money-free models of governance and collective sufficiency. Life Without Moneyis written by high-profile activist scholars, including Harry Cleaver, Ariel Salleh, and John O'Neill, making it an excellent text for political economy and environmental courses, as well as an inspiring manifesto for those who want to take action